CX3CR1 polymorphisms and the risk of age-related macular degeneration - Ma, Baofeng (Int J Clin Exp Pathol, 2015)
Background: Age-related macular degeneration (AMD), a most common eye disease, can lead to irreversible visual impairment. Age, genetic and environmental factors have been implicated in AMD. Chemokine (C-X3-C motif) receptor 1 (CX3CR1) gene polymorphisms could influence the susceptibility of AMD. Methods: We tested the association between AMD and single nocleotide polymorphisms (SNPs) of CX3CR1 gene (rs3732378 and rs3732379) in 102 cases and 115 controls from China. Genotypes were determined by MassArray genotyping assay method. Association between CX3CR1 gene polymorphisms and AMD were examined by χ(2) test and logistic regression. Results: Genotype distribution of CX3CR1 gene polymorphisms were in accordance with HWE examination. No obvious differences were observed in the genotypes of rs3732378 polymorphism between case and control groups (P>0.05), but A allele of it could increase the risk of AMD (P=0.025, OR=2.391, 95% CI=1.092-5.237). Both TT genotype and T allele of rs3732379 were significantly associated with the susceptibility of AMD (P=8.663, OR=8.663, 95% CI=1.044-71.874; P=0.021, OR=2.076, 95% CI=1.104-3.903). Age, gender and smoking status were used as common confounders to adjust the association between CX3CR1 gene polymorphism and AMD risk. Then we found that rs3732378 had no obvious association with AMD susceptibility. TT genotype of rs3732379 related to the occurrence of AMD, but the association was not significant (P=0.050, OR=8.274, 95% CI=1.002-69.963). T allele of rs3732379 might increase the susceptibility of AMD (P=0.029, OR=2.033, 95% CI=1.077-3.838). Conclusion: T allele of rs3732379 might have a positive association with the susceptibility of AMD.